Futurologi Bahasa Aceh: Kajian Arkais dan Ancaman Kepunahan dalam Perspektif Linguistik dan Budaya - Istiqamah Istiqamah; Hayatul Muna; Naufa Rayluna; Nurfadilla Nurfadilla (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
This study explores the future of the Acehnese language through a linguistic futurology lens, focusing on the existence of archaic vocabulary as both a linguistic heritage and an indicator of language endangerment. Rich in historical, cultural, and local identity values, the Acehnese language is experiencing decline due to weakened intergenerational transmission, the dominance of national and global languages, and the lack of preservation policies. Using a descriptive qualitative approach, data were collected through observations, interviews, and questionnaires involving 25 native speakers. The findings identified 82 archaic words categorized into nouns, verbs, and adjectives, reflecting traditional activities, local culture, and human–nature relationships. Based on UNESCO’s language vitality indicators, Acehnese is classified as vulnerable. The threats include decreased usage in public and digital spaces, limited documentation and educational resources, and shifting language attitudes. This study highlights the urgency of revitalizing the Acehnese language through educational integration, comprehensive documentation, and sustainable preservation policies to maintain regional languages as an essential part of national cultural identity.